Velfærdsstatens krise og neoliberalismens indtog i Danmark i 1970’erne - Olsen, Niklas (Slagmark - Tidsskrift for idéhistorie, 2020)
This article traces the rise of neoliberalism in Denmark to the so-called crisis of the welfare state in the early 1970s, where a new liberal offensive was launched within the ranks of Venstre – The Liberal Party of Denmark. The article shows how new liberal ideas were launched by a generation of politicians who all connected the crisis of the welfare state to a growing public sector, which they regarded as inefficient and undemocratic. In the attempt to counter the crisis in question, they did not aim to abolish the welfare state but to reduce its size and change its content. The aim was first of all to create competition in the public sector. In this process, the liberal politicians launched new ideas concerning decentralization, free choice in the public sector, and economic growth, which formed the pillars of the new liberalism that was developed within Venstre in the 1970s.